ANALYSIS OF FINANCIAL SECURITY RESEARCH VECTORS: BIBLIOMETRIC ANALYSIS AND VISUALIZATION - CHORNA, Svitlana (Scientific journal «World of Finance», 2023)
Introduction. Bibliometric analysis allows the identification of major trends and priority research areas, as well as the identification of reputable scientists and their contribution to the field. Using the software package VOSviewer v.1.6.14, we analysed the common use of keywords in publications and the identification of partner countries, selecting the two most popular scientific databases Scopus and Web of Science as search tools.The purpose of the article is to identify trends and vectors of scientific research on financial security in order to identify the main directions in related fields. The bibliometric analysis of publications related to finance, economics and security made it possible to identify areas of research in this field and to formulate a quality policy aimed at strengthening national security and improving economic regulation.Results. With the development of technology and the globalisation of the information environment, the number of studies on the topic has increased. The number of relevant research indicators was taken from the Scopus database - 1970 literature, WoS - 1936.. Financial security is studied in several disciplines. According to the Scopus database, the most relevant fields are social sciences, economics, econometrics and finance. According to WoS, financial security is studied within the field of business and finance. Results are also provided for the most cited publications. Researchers from the USA, UK, China, Canada, Australia, Ukraine and Germany have contributed most to the development of this field. The results of the bibliometric analysis showed that there were 8 data clusters from the Scopus database and 11 data clusters from the WoS database.Conclusions. The study revealed the growing interest of the scientific community in the analysis of financial security issues. The direction of scientific research leads to the conclusion that financial security affects all areas of the economic environment and quality of life. A bibliometric analysis of publications by keywords shows that the concept of financial security is often associated with other concepts. This shows that the concept often coincides with categories such as economy, security, environment, etc. The results obtained allow us to determine the vector of focus for further assessment of the country’s financial security.